2021
DOI: 10.3389/fmicb.2021.758061
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Natural Selection of Plasmodium vivax Duffy Binding Protein-II From China-Myanmar Border of Yunnan Province, China

Abstract: Malaria incidence has declined dramatically over the past decade and China was certified malaria-free in 2021. However, the presence of malaria in border areas and the importation of cases of malaria parasites are major challenges for the consolidation of the achievements made by China. Plasmodium vivax Duffy binding protein (PvDBP) performs a significant role in erythrocyte invasion, and is considered a promising P. vivax vaccine. However, the highly polymorphic region of PvDBP (PvDBP-II) impedes the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The haplotype diversity of pvdbp II from the northwestern Thailand population (Hd = 0.849 ± 0.024) was comparable to that reported from eastern Myanmar (0.850 ± 0.021) using specimens collected in 2016 ( Hu et al, 2019 ). Most (12/14) SNPs detected on pvdbp II in this study have been reported previously ( Almeida-de-Oliveira et al, 2020a ; Hoque et al, 2018 ; Hu et al, 2019 ; Shi et al, 2021 ). In contrast, many novel mutations were found in pvmsp1 42kDa , consistent with its higher global diversity and greater capacity to accommodate mutations.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…The haplotype diversity of pvdbp II from the northwestern Thailand population (Hd = 0.849 ± 0.024) was comparable to that reported from eastern Myanmar (0.850 ± 0.021) using specimens collected in 2016 ( Hu et al, 2019 ). Most (12/14) SNPs detected on pvdbp II in this study have been reported previously ( Almeida-de-Oliveira et al, 2020a ; Hoque et al, 2018 ; Hu et al, 2019 ; Shi et al, 2021 ). In contrast, many novel mutations were found in pvmsp1 42kDa , consistent with its higher global diversity and greater capacity to accommodate mutations.…”
Section: Discussionsupporting
confidence: 68%
“…Amino acid changes were found at various positions in both parasite proteins. Of 131-aa in the pvdbp II fragment, 14 were mutated, 12 of which (K326E, N330D, G339D, E340K, K341N, H345R, S353T, T359R, N372K, I374M, I379L, W392R; numbers referenced to the P01 strain) had been previously reported from Brazil ( Almeida-de-Oliveira et al, 2020a ), Myanmar ( Hu et al, 2019 ), Sudan ( Hoque et al, 2018 ), and China ( Shi et al, 2021 ) ( Fig. 4D ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations